Manfaat Discharge Planning pada Pasien CVA Infark : A Systematic Review - Fetreo Negeo Putra; Nursalam Nursalam; Aang Kunaifi (FORIKES, 2021)
Background: Discharge planning is a systematic process and pilot of various case that needs continous trearment, for example is CVA infarct. Objective: To find out the function of discharge planning on CVA infarct patient. Method: The database used in this study were Scopus, SAGE and Pubmed were limited to the last 6 years of publication from 2014 to 2020, full-text articles and in English. The keyword used were